PELAKSANAAN PROGRAM PEMBERDAYAAN SOSIAL DAN PENANGANAN FAKIR MISKIN OLEH DINAS SOSIAL KABUPATEN SIAK TAHUN 2018 - Tomas Sugianto; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Poverty creates various social problems caused by poverty itself. The problem of poverty is the source of many other social problems such as crime, unemployment, stupidity, low health levels, and others. Poverty management is also regulated in Law no. 13 of 2011 concerning Handling the Poor. Poverty alleviation is one of the government's tasks, where in Presidential Regulation Number 96 of 2015 concerning the Acceleration of Poverty Reduction article 1 states that poverty alleviation is government and regional government policies and programs that are carried out in a systematic, planned and synergized manner with the business world and society to reduce the number of poor population in order to increase the degree of welfare. The poverty line in Siak Regency from 2016 to 2018 continues to increase, this can be seen from the data released by the Siak Regency Central Bureau of Statistics. This research was conducted with the first objective, to describe the Implementation of the Social Empowerment and Handling of the Poor Program by the Social Service of the Siak Regency in 2018. Second, to find out the inhibiting factors for the Implementation of the Social Empowerment and Handling of the Poor Program by the Social Service of the Siak Regency in 2018. In This study uses a qualitative approach, and this type of research is descriptive, data collection techniques by conducting interviews, and using competent sources/informants. The results that can be concluded from this research are that the Implementation of the Social Empowerment Program and Handling the Poor by the Siak Regency Social Service in 2018 has not been implemented optimally, because there are still deficiencies in social empowerment program services and handling the poor so that future empowerment is not implemented for the community poor. Keywords: Implementation, Empowerment Program, Poverty.